Une tragédie pour Gaspard de Coligny, nouveau Pompée ? - Guðrún Kristinsdóttir-Urfalino (Etudes Epistémè)
The play Tragédie nouvelle appelée Pompée en laquelle se voit la mort d’un grand Seigneur, faite par une malheureuse trahison [A New tragedy called Pompey, in which we see the death of a great Lord, caused by an unfortunate betrayal], was published in Lausanne, Switzerland, in 1579 by an anonymous author. The tragedy tells the story of the great Roman general Pompey, leader of the republican camp, assassinated and beheaded, betrayed for having trusted the young Egyptian king Ptolemy, surrounded by ill-intentioned advisors. As represented in the play, the circumstances of Pompey’s fall recall the conditions of the assassination of Admiral Gaspard de Coligny, which was the first act of the Saint Bartholomew’s Day massacres.Several aspects of the poetics of the play suggest that the tragedy was written as a memorial in honour of the Admiral Coligny. The ambition of this article is to establish the plausibility of this conjecture.The first part is devoted to the poetics of the play ; the second, to the memory restoration work initiated by the first historians of the Saint Bartholomew’s Day massacres. The third part presents the set of clues towards the plausibility of the hypothesis. The Roman examplum of the fall of Pompey seems to have provided an allegorical material for a quasi topical tragedy evoking the conditions of the assassination of Admiral Coligny.